THE DEVELOPMENT OF THE RAKYAT'S COFFEE CLUSTER IN BONDOWOSO THE NEW NORMAL ERA - Edhi Siswanto Siswanto (POLITICO, 2022)
The research was conducted to see the Community Coffee Cluster Development Program in the Pandemic Period and the New Normal Era. The People's Coffee Cluster experienced a decline in sales during the pandemic, a community empowerment program developed by the Bondowoso Regency government and the Plantation Sector of the Bondowoso Regency Agriculture Service with the Bondowoso branch of the East Java Bank, the Jember Coffee and Cocoa Research Center, Perum Perhutani, and the Indonesian Coffee Farmers Association. Bondowoso branch. The People's Coffee Cluster Program is a policy for empowering coffee farmers in Bondowoso Regency, which aims to raise the low quality of coffee quality in Bondowoso and make it one of the drivers of the community's economic welfare. In this study, the data obtained is qualitative data that describes certain social phenomena. The method used in this research is qualitative descriptive analysis. The results showed that the implementation of the People's Coffee Cluster Program in Bondowoso Regency during the pandemic period needed attention in the marketing and production processes. Changes in SOPs in the development of the People's Coffee Cluster were carried out not only to increase sales and production but for the survival and economic stability of the Smallholder Coffee Growing Farmers during the epidemic period.